Ways of expressing emotions in propagandistic communications verbal-visual (on the example of the covers of opinion weeklies) - Szkudlarek-Śmiechowicz, Ewa (Papers in Linguistics, 2019)
The aim of the article is to describe the mechanisms of expressing emotions (and therefore valuating) ​​in ideologized verbal-visual communications (texts), which constitute a definite, usually unambiguous, axiological interpretation of the world. The covers of newsweeklies, which are propaganda communications/ texts, are aimed not at changing attitudes or views of the recipient, but at accepting or rejecting the implicated axiological-emotive opinions. Relations between emotions and values ​​are showed in the article from the point of view of psychology of emotions (in the introductory part) and linguistic communication (in the analytical part). First of all, the structure of the visual-verbal layer of the covers was analyzed, which is mostly based on a simple predicative scheme (X is Y), creating propaganda word-picture labels. In the end of article, attention was paid to the names of emotions and visual symbols of emotions contained on the covers. Analytical and exemplification material are the front pages of four newsweeklies from 2016 and 2017: “Newsweek”, “Polityka”, “Do Rzeczy”, “W Sieci” (“Sieci Prawdy”).